Rationalization Study of Rainfall Network Density Using The Kagan-Rodda Method in Sub Watershed of Bango - Azhari, Zeinnia Alya; Limantara, Lily Montarcih; Fidari, Jadfan Sidqi (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2022)
Management of water resources in watershed determined by avaibility of accurate rainfall data. The study of rationalization rainfall recorded density result the suggestion of amount and placement of rainfall recorded in watershed. The study was manage in Watershed of Bango with total area 246,4 km2 using Kagan-Rodda method and WMO Standard. The analysis of rainfall recorded using WMO Standard, 100-250 km2/rainfall recorded shown that none of the existing rainfall recorded in Bango Sub-Watershed are qualified. The result of Kagan-Rodda analysis giving recommendation the precise amount of rainfall recorded in Bango Sub-Watershed is Blimbing as point of reference station and form another rainfall recorded, C station. The coverage area of Blimbing is 133,74Â  km2 and C Station is 112,61 km2.